THE SECRET OF THE BEAUTY OF THE SPEECH OF THE PROPHET - Fatıma Zahra NAHMAR (Fırat University, 2019)
The Prophet, may Allah's peace and blessings be upon him, singled out a number of characteristics in which the Prophets, Messengers, and Creation were distinguished by the most important of which is the Prophet's Hadith. This is in honor of his position and honor for his position. And the impact of the human, scientific, spiritual and moral perfection of the Prophet (PBUH) at the height of his position, addresses the following problems: What is the secret of the aesthetics of the Prophet's statement? And what made him influential in the soul?